Relationship between driver gene mutations and clinical pathological characteristics in older lung adenocarcinoma - Liu, Xia; Jiang, Guopeng; Sun, Xuefei; Su, Guangfeng; Zhang, Xuan; Shen, Dan; Yan, Na (Frontiers in Oncology, 2023)
Objectives: This study aims to investigate the mutation characteristics of LUAD diver gene and its relationship with clinicopathological features in older LUAD. Materials and methods: A total of 275 patients were diagnosed as LUAD and were over sixty years old. We utilized next-generation sequencing technology to detect and analyze gene mutations in postoperative tissue specimens, including EGFR, KRAS, ALK, ROS1, RET, MET, BRAF, HER2, PIK3CA and NRAS. Results: A total of 90.18% (248/275) of older LUAD patients experienced genetic mutations. The EGFR (192, 69.82%) had the highest mutation rate among ten genes, followed by KRAS (21, 7.64%), MET (21, 7.64%), ERBB2 (15, 5.45%), RET (9, 3.27%), ALK (8, 2.91%), ROS1 (8, 2.91%), PIK3CA (6, 2.18%), BRAF (5, 1.82%) and NRAS (1, 0.36%). We also found thirty patients (15.63%) with EGFR mutations also having other gene mutations. The L858R mutation and exon19 deletion were the predominant EGFR mutations, accounting for 84.90% of EGFR-mutated patients. In addition, fifty-one kinds of EGFR mutations were detected, distributed in the protein tyrosine kinase catalytic domain (43, 84.31%), cysteine enriched domain (4, 7.84%), receptor binding domain (3, 5.88%), and EGFR transmembrane domain (1,1.96%). Ten cases of gene fusion mutation were detected. Two rare partner genes, PKHD1 (P60:R34) and STK39 (R33:S11), were detected by ROS1 gene fusion. RET gene fusion revealed a rare companion gene KCND2 (R11:K2). The EGFR mutations were more prevalent in female, non-smoking patients (p < 0.05), and the KRAS mutations were more common in male and smoking patients (p < 0.01). In addition, the BRAF mutations were more likely to occur in the right lung (p < 0.05). Conclusion: Older LUAD populations exhibit diverse genetic mutations, which may also exist simultaneously. Simultaneous detection of multiple genes by NGS can accelerate and enhance targeted treatment benefits for older LUAD patients, ultimately improving their quality of life.